Ta'sir Wasail al fiidiiyu Youtube Podcast al 'Arab 'ala Nataa'ij Ta'allum al Lughah al 'Arabiyyah li Thullab al Shaf al 'Asyir fi al Madrasah al Tsanawiyah al Islamiyah al Mu'ammiliiyah li Jami'ah al Hukumiyah al Islamiyah Sumatra al Syimaliyah Medan - Marpaung, Mhd Haical Eriyanto; Rahmaini (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
This study aims to determine the effect of using YouTube Arab Podcast video media on the Arabic learning outcomes of tenth-grade students at MA Laboratorium UINSU Medan. The background of this research stems from the low interest and achievement in learning Arabic, which is caused by monotonous conventional teaching methods. The study employed a quantitative approach with a quasi-experimental design using cluster sampling, involving a control class and an experimental class. Data were collected through pretests and posttests and analyzed using an independent t-test. The results showed a significant improvement in the learning outcomes of students who used Arab Podcast video media compared to those who learned without video media, with a significance value of 0.039 < 0.05. This indicates that the use of YouTube-based video media is effective in improving students’ understanding of vocabulary, sentence structure, and Arabic pronunciation. Thus, interactive digital media such as Arab Podcast can serve as an alternative learning strategy relevant to the needs of students in the digital era.